Relevansi Kompetensi Teknik Gambar Manufaktur di SMK Terhadap Kebutuhan Industri - Ahmad Nur Arifin; Febrianto Amri Ristadi (Department of Mechanical Engineering Education, 2017)
This research aims to identify the relevance of competency of manufacture drawing subject at SMK Muhammadiyah 2 Jatinom compared to the industrial competency needs. The research is a descriptive research. The subjects of the study were students, a teacher of manufacture drawing subject, and drafters working in the manufacturing industry. Questionnaires were used as data collection method. Data were analyzed using statistical descriptive analysis by percentages. The result shows that the relevance of competency of manufacture drawing subject to the industrial competency needs is 74.3%, which is in the category of